Implementation of the Merdeka Curriculum in Realizing Quality Learning in Schools - Iyan, Iyan (International Journal of Education, Culture, and Society, 2026)
This study aims to examine how the implementation of the Merdeka Curriculum supports the creation of quality learning in schools and to identify the opportunities and challenges that emerge during its implementation. The Merdeka Curriculum provides teachers with greater flexibility to design learning activities aligned with students’ needs, thereby promoting a more meaningful, active, and student-centered learning process. This study employed a qualitative method using a literature study approach by collecting data from reliable sources, including scientific journals, books, and official documents related to the Merdeka Curriculum. The collected data were analyzed descriptively to obtain a comprehensive understanding of how the curriculum is implemented in school contexts. The findings indicate that the implementation of the Merdeka Curriculum has significant potential to improve learning quality, particularly through project-based learning, the strengthening of character in accordance with the Pancasila Student Profile, and teacher autonomy in selecting appropriate instructional strategies. However, its implementation continues to face several challenges, including limited teacher understanding of the curriculum concept, inadequate readiness of supporting facilities, and the need for continuous professional development. This study concludes that collaboration among the government, schools, and teachers is essential to ensure optimal curriculum implementation and to promote more effective, creative, and high-quality learning.